Enhancing Aerobic and Sprint Performance Through Weighted Vest-Based Anaerobic Soccer Training: Evidence From a Controlled Trial in Soccer Players - Vebrianto, Dimas Hamdhan; Nugraha, Afif Dwi; Triardhana, Yanuar Alfan; Andriana, Laily Mita; Kusuma, I Dewa Made Aryananda Wijaya (Physical Education Theory and Methodology, 2026)
Background. Modern soccer requires repeated high-intensity, complex movements, making aerobic performance essential for players. Objectives. This study aimed to examine the effect of Anaerobic Soccer Training (AnST) utilizing a weighted vest (WV) weighing 7.21 ± 0.72% of body mass on aerobic performance, measured by VO2max and speed. Materials and Methods. This study employed a quasi-experimental design with two groups (Group A and Group B), utilizing a pre-test as a covariate and a post-test as the dependent variable. A total of 22 male soccer players were randomly divided into two groups: a control group with an additional load of 0% of body weight (Group A, n = 11) and an experimental group with an additional load of 7.21 ± 0.72% of body weight (Group B, n = 11). Aerobic performance was assessed using the Yo-Yo Intermittent Recovery Test Level 1 (YYIR1) before and after a three-week intervention involvingfour sessions per week. The YYIR1 results provided VO₂max and speed data for analysis. Statistical tests included the Shapiro–Wilk normality test, Levene’s homogeneity test, and Quade’s Non-parametric Analysis of Covariance using IBM SPSS 30 with a 0.05 significance level. Results. Based on the results obtained using Quade’s Non-parametric Analysis of Covariance, significant differences were found between groups A and B in terms of VO₂max (p = 0.015) and speed (p = 0.005) after controlling for pre-test values. These results indicate that the types of training given to each group had different effects on improving the players’ aerobic performance and speed. Conclusions. The findings confirm that three weeks of AnST with a weighted vest of 7.21 ± 0.72% of body mass may enhance VO₂max and running speed. However, these results are preliminary and should be interpreted with caution due to the short duration and small sample size.